An experimental study on low-velocity nonlinear flow in vuggy carbonate reservoirs. Issue 4 (3rd July 2016) - Wu, Haitao; Li, Fujun; Liu, Jiawen; Chen, Jiang; Lv, Xiaowei; Hu, Wei
Abstract: Vuggy carbonate reservoirs in the Middle East, which have characteristics such as high porosity, low permeability, and few fractures, are significantly different from fractured-vuggy carbonate reservoirs. In this study, single-phase flow experiments and core mercury injection experiments were conducted to analyze the pore size distribution and low-velocity nonlinear flow characteristics of vuggy carbonate rocks in Halfaya oilfield. The results show that the relationship between pseudo-threshold pressure gradient and permeability in matrix carbonate rocks is linear. However, vuggy type does not exhibit the same linear relationship. Compared with matrix type, vuggy carbonate rock has a nonlinear flow zone when the pressure gradient is comparatively low and the nonlinear flow characteristics are quite different from those of low-permeability sandstone reservoirs. Because of the multi-polarization of flow channel radius in vuggy carbonate rocks, fluid stepwise starts flowing as the pressure gradient increases. Vuggy carbonate rock has a pseudo-threshold pressure gradient during the low-velocity flow, but the actual threshold pressure gradient does not exist. The concept of whole channel flow pressure gradient is presented in this paper. The results contribute to improve the understanding of low-velocity flow characteristics of vuggy carbonate reservoirs.